Identification and Antimicrobial Resistance of Enterococcus Spp. Isolated from the River and Coastal Waters in Northern Iran. (26th November 2014) - Alipour, Majid; Hajiesmaili, Reza; Talebjannat, Maryam; Yahyapour, Yousef
Abstract : As fecal streptococci commonly inhabit the intestinal tract of humans and warm blooded animals, and daily detection of all pathogenic bacteria in coastal water is not practical, thus these bacteria are used to detect the fecal contamination of water. The present study examined the presence and the antibiotic resistance patterns of Enterococcus spp. isolated from the Babolrud River in Babol and coastal waters in Babolsar. Seventy samples of water were collected in various regions of the Babolrud and coastal waters. Isolated bacteria were identified to the species level using standard biochemical tests and PCR technique. In total, 70 Enterococcus spp. were isolated from the Babolrud River and coastal waters of Babolsar. Enterococcus faecalis (68.6%) and Enterococcus faecium (20%) were the most prevalent species. Resistance to chloramphenicol, ciprofloxacin, and tetracyclin was prevalent. The presence of resistant Enterococcus spp. in coastal waters may transmit resistant genes to other bacteria; therefore, swimming in such environments is not suitable.